Perbandingan kritik Ushul Nahwu: Pemikiran Tamam Hasan dan Ibrāhīm Muṣṭafā - Muflihah, Sayyidatul; Qodriyah, Uswatul (Maliki Interdisciplinary Journal, 2024)
Nahwu science, a field that studies Arabic grammar, has attracted attention of observers and scholars of Arabic language from classical to modern times. Since Abu Aswad ad-Duali’s era, the field has experienced a significant development and has become an important basis for understanding Arabic in depth. Classical studies that are philosophical and logical, such as those of Imam Sibawaih, have provided an epistemological basis for the development of nahwu science. In an effort to understand the significant differences in their perspectives, this article compares and analyzes the thoughts of these two figures. Tamam Hasan criticized several aspects of nahwu from the point of view of dialect, epochal theory, history, and the method of proof. Sebaliknya, Ibrāhīm Muṣṭafā presented a fundamental criticism of the inconsistency of the meaning of classical nahwu with modern studies, especially in the concept of I’rab. Therefore, Ibrāhīm Muṣṭafā and Tamam have their own way of thinking.